PENGGUNAAN KARTU HURUF BERGAMBAR DALAM PEMBELAJARAN MEMBACA PERMULAAN PADA ANAK KELOMPOK B RA SIRRUL KHULUQ KECAMATAN SINGOSARI KABUPATEN MALANG - Juwanis Fatul Rizana; Mohammad Afifulloh; Ika Anggraheni (Jurnal Dewantara, 2021)
This study uses Classroom Action Research (CAR) to determine the early reading ability of children in group B RA sirrul khuluq, Singosari district, Malang district. The CAR method is used for action research by teachers carried out in classroom learning, with the subject of children aged 5-6 years, based on the results of research and data collection techniques by triangulation (interviews, observations, documentation). 1) This research was carried out in two cycles including: 1) planning including preparing RKH (Daily activity plan), determining themes, preparing media, preparing research instruments. 2) Implementation in accordance with RKH (initial activity, core activity, closing activity), 3) Observation, (4) Analysis and Reflection Stage. The ability to read in the first cycle was declared complete (15.625%), the second cycle (91.14%). The conclusion of this research is that illustrated letter card media is proven to improve the reading ability of children in Group B RA Sirrul Khuluq, Singosari District, Malang Regency.